Avaliação In Silico de marcadores moleculares da resposta imunológica associados ao estresse de aves - Lara, Lucas Januzzi (2016)
Stress can be characterized an unspecific response for any challenge such as beak trimming, thermic discomfort, social issues, feed privation, etc. Is known that stress modify poultry immune response and increases pathogen infections leading to economic losses caused by production and reproduction delay. Studies have been done to identify different proteins expressions under stress on different species. However, poultry did not have those stress modulation and alteration by stress elucidated. Therefore the aim of this study was investigated expressed stress molecular markers on poultry. Were selected 15 mRNA genetic sequences related to immune system. Results showed a non-homology between poultry and mammals sequences. From 15 sequences, 5 could not be predicted because they were more than 2500 nucleotides; from the other 10 sequences the analysis showed 20 conformational structure per each and the most stable sequence were accept by the Minimum Free Energy. The highest antigenic epitope were accepted by the maximum score, a total of 8934 epitopes were predicted and 15 were taken. These results will support future studies to expand understanding on how stress can modulate the immune system and possibilities to have a rapid diagnostic, helping on increasing animal welfare, biosecurity and productivity.